PCM embedded square channel receiver for effective operation of Net Zero Emission/Energy PDC building heating system - Sathish T.; Saravanan R.; Esther Jeyanthi C.; Sabariraj R.V.; Hemachandu P.; A?bulut .; Ahamed Saleel C.; Soudagar M.E.M. (Elsevier Ltd, 2024)
Net Zero Emission / Energy recommends reducing energy consumption to zero (use of renewable sources) and ensuring no pollution and emissions. Parabolic Dish Collector (PDC) is such a device, which utilizes the Solar energy (Zero Cost of Energy) for heating (Zero Emission of Carbon gases) by converting solar energy into heat transfer fluids (HTF). The recent researches PDC receiver's efficiency improvement by different designs or arrangement inside the receiver as well as different types of phase change materials (PCMs) incorporated to it. This investigation aims to improve the PDC by involving the square channel type solar receiver as an alternate receiver and embedding it with the PCM for building heating applications. The thermal performance of 14 m2 square-channeled PDC was investigated with and without PCM embedded conditions. For embedding PCM of Paraffin wax, 3 kg was used in thermal storage in this experiment. The square-channeled receiver recorded the lowest receiver surface temperature and the highest discharge water temperature. Black coating is employed to reduce the heat loss from the receiver substance. The average energy and exergy efficiencies are around 65.8 % and 6.8 %, respectively, at a flow velocity of 0.07 kg/s. As PCM maintains a constant temperature, the solar receiver can hold its internal temperature around triple times higher than the conventional PDC (without PCM case). Hence it was experimentally ensured that PCM-filled PDC (solar receivers) is suitable for heating applications in domestic and industrial buildings. 2023 Elsevier Ltd